Attracting future civil servants with public values? An experimental study on employer branding. Issue 5 (2nd September 2020) - Weske, Ulrike; Ritz, Adrian; Schott, Carina; Neumann, Oliver
Abstract: A frequently cited recommendation of public service motivation (PSM) research is to use PSM in the context of HR marketing. However, empirical evidence demonstrating the usefulness of addressing PSM in the recruitment process is limited. Moreover, we know little about the relative importance of PSM for public employers' attractiveness. We address this gap using an experimental research design to investigate whether public service motivated individuals differ from extrinsically motivated individuals in terms of their attraction to organizations that emphasize either "traditional" public or private values in their employer branding. Our findings indicate that public service motivated individuals are attracted neither to public nor to private values in employer branding. Furthermore, individuals with very high levels of extrinsic motivation are more attracted to private values employer branding than to public values employer branding and to the control group.